2008
DOI: 10.3748/wjg.14.2388
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric mucosa associated lymphoid tissue lymphoma: Clinical data predicted treatment outcome

Abstract: AIM:To determine clinical characteristics and treatment outcome of gastric lymphoma after chemotherapy and immuno-chemotherapy. METHODS:Thirty four patients with primary gastric mucosa associated lymphoid tissue (MALT) lymphoma (Ann Arbor stages Ⅰ to Ⅳ) were enrolled. All had upper gastric endoscopy, abdominal ultrasonography, CT and H pylori status assessment (histology and serology). After anti-H pylori treatment and initial chemotherapy, patients were re-examined every 4 mo. RESULTS:Histological regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Helicobacter pylori has been recognized as the most common cause of chronic gastritis and considered to be the putative causative agent of gastric and duodenal ulcers, gastric adenocarcinoma, and gastric extranodal marginal zone B cell lymphoma (eMZBL) of the MALT type [6]. A possible causal relationship between GP and the underlying H. pylori infection has also been reported [7,8].…”
Section: Discussionmentioning
confidence: 98%
“…Helicobacter pylori has been recognized as the most common cause of chronic gastritis and considered to be the putative causative agent of gastric and duodenal ulcers, gastric adenocarcinoma, and gastric extranodal marginal zone B cell lymphoma (eMZBL) of the MALT type [6]. A possible causal relationship between GP and the underlying H. pylori infection has also been reported [7,8].…”
Section: Discussionmentioning
confidence: 98%
“…Feldman et al14 reported that ESR and CRP were very highly correlated (P<0.001). High ESR also has been found to correlate with overall poor prognosis for various types of cancer, including Hodgkin's disease, gastric carcinoma, renal cell carcinoma, breast cancer and mucosa associated lymphoid tissue (MALT) lymphoma lymphoma 13,15. According to meta-analysis on renal cell cancer patients, ESR was revealed to be a better indicator of cancer-specific survival than CRP 16.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that the infected individuals, who had various symptoms, including pain, did not suffer from the pain more than the individuals, who did not have an infection at all (RiazulHassan S 2007). This aggravates the condition more, as the infected part of the population is more likely to postpone a visit to the doctor, since their symptoms are not severe enough that increases the probability of infection spreading (Todorovic M, 2008,).…”
Section: Resultsmentioning
confidence: 99%